Evaluate the following expression:
-X- 6x + 10 when x = 5
1 answer:
Answer:
-25
Step-by-step explanation:
Evaluate -x - 6 x + 10 where x = 5:
-x - 6 x + 10 = -5 - 6×5 + 10
-6×5 = -30:
-5 + -30 + 10
-5 - 30 + 10 = 10 - (5 + 30):
10 - (5 + 30)
5 + 30 = 35:
10 - 35
10 - 35 = -(35 - 10):
-(35 - 10)
| 3 | 5
- | 1 | 0
| 2 | 5:
Answer: -25
You might be interested in
Answer:
Step-by-step explanation:
2x - 9y = 23
5x - 3y = -12x - 9y = 23we]periyhw[euiorghweuirtg7wuio[ryg
5x - 3y = -12x - 9y = 23
5x - 3y = -12x - 9y = 23
5x - 3y = -1
Step-by-step explanation:
log(x+2)-log(x-1)=log2
log(x+2)/(x-1)=log2
=> (x+2)=2(x-1)
=>x+2 =2x-2
=> x=4
Ok Ok Ok Ok Ok Ok Ok Ok Ok
Answer:
Step-by-step explanation: